Koreografi Tari Piriang Indang Nan Badantiang Sanggar V Tunang Kecamatan Naggalo Kota Padang (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study aims to reveal describe and analyze the choreography of Piriang Indang Nan Badantiang Dance in Sanggar V Tunang, Nanggalo District, Padang City. This research using qualitative methods is research that uses a naturalistic approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out using literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusion. The results showed that cultivation is certainly inseparable from the creative process of wanting to develop a new motion and paying attention to the exploration of motion. After discovering the idea of the Indang Nan Badanting Piriang Dance the choreographer contemplates in a sound or term the vernacular in a dance that is often performed can become a dance title. The motion created by the choreographer comes from the existing motion and is redeveloped to be more widespread and different even though the performance performs the same or repetitive movements, but can be distinguished in the composition and cultivation. This Indang Nan Badantiang Piriang Dance has a dominant element of space having straight and curved lines, low and medium levels, front and side facing directions, medium and large volumes, and front and side view focus. According to the choreographer, the creation of the Piriang Badantiang Indang Dance was also inspired by the existing Piriang Dance movements but redeveloped so that they are not the same.